Channel-wall functionalization in covalent organic frameworks for the enhancement of CO2 uptake and CO2/N2 selectivity. Issue 45 (19th April 2016) - Zhao, Shang; Dong, Bin; Ge, Rile; Wang, Chang; Song, Xuedan; Ma, Wei; Wang, Yu; Hao, Ce; Guo, Xinwen; Gao, Yanan
Abstract : Two structurally similar groups with one being CO2 -philic but the other not were anchored into the channel walls of 2D COFs. The decreased surface area of COFs undoubtedly decreased CO2 adsorption if too many functional groups were introduced. Abstract : A series of tailored covalent organic frameworks (COFs), i.e. [NN] X % –TAPH-COFs and [CC] X % –TAPH-COFs, were synthesized by post-fabrication of [HO] X % –TAPH-COFs with 4-phenylazobenzoyl chloride (PhAzo) and 4-stilbenecarbonyl chloride (PhSti), respectively. Powder X-ray diffraction (PXRD), FT-IR, and solution-state 1 H NMR of the digested COFs were applied to clarify the functional groups integrated in the pore channels. Gas sorption isotherms confirmed that the [NN] X % –TAPH-COFs and [CC] X % –TAPH-COFs had moderate surface areas, narrow pore sizes, and good physicochemical stability. Compared with [CC] X % –TAPH-COFs, the [NN] X % –TAPH-COFs exhibited higher CO2 uptake capacities of up to 207 mg g −1 (273 K and 1 bar), isosteric heats of adsorption for CO2 (30.7–43.4 kJ mol −1 ), and CO2 /N2 selectivities of up to 78 (273 K) because of the dipole interactions between the azo group and CO2 as well as the N2 -phobic behavior of the azo group. Furthermore, although the decreased pore size was advantageous for increasing CO2 adsorption, the decreased surface area of the COFs would undoubtedly decrease CO2 adsorption if too many functional groups were introduced.